Pemikiran Hukum Islam Imam Malik Bin Anas (Pendekatan Sejarah Sosial) - Danu Aris Setiyanto (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2016)
The study in this paper is focused thinking Islamic law Imam Malik bin Anas approach to social history. This study is a study that is fairly new in the field of science of Islamic law, so it is still a bit of academics watched. Imam Malik himself was one of four priests schools are known by the nickname ahlu hadith. Imam Malik in his life has never been out of the city of Medina except during Hajj. This of course support his thought in solving the complexity of the problems largely solved by the hadith enough. In addition, the state of the environment in the Medina which is the place where the Prophet lived for several years, community issues are lightweight and simple. Although Imam Malik called a hadith expert, but he also remains unaffected by the use of ratios in berijtihad because the social conditions at the time. This is evidenced by the use of expert Amal Madinah (Medina community of practice), Fatwa Sahabah, Qiyas, Al-maslahah mursalah, Ad-dari'ah, Al-'Urf (custom) in making Islamic law. Imam Malik was also like other schools with the Qur'an and Hadith as the primary source of Islamic law.